College Students’ Prevalence of Sleep Hygiene Awareness and Practices - Felix, Victoria A; Campsen, Nathalie A; White, Abbey; Buboltz, Walter C (Advances in Social Sciences Research Journal, 2017)
Research has consistently found that college students report short sleep length and poor sleep quality. As a result of their poor sleep quality, there is concern that college students may struggle with issues associated with academic performance, physical health, and mental health. Previous research has investigated a multitude of factors that may contribute to poor sleeping behaviors, including sleep hygiene awareness and practices. The current study found that participants were obtaining less than the recommended average hours of sleep. Results indicated an almost equal number of participants reported poor sleep quality, average sleep quality, and good sleep quality. Results also indicated that between 40-50% of the sample reported difficulties related going to bed, falling asleep, maintaining sleep, reinitiating sleep, and returning to wakefulness. Although participants in the present study reported sleep hygiene awareness, their knowledge is not associated with their sleep practices. Based on these results, it may be implied that improving or increasing sleep hygiene knowledge is not an intervention that would be effective in improving sleep hygiene practices.